2016
DOI: 10.1159/000445318
|View full text |Cite
|
Sign up to set email alerts
|

Increased Intracranial Pressure in a Boy with Gorham-Stout Disease

Abstract: Gorham-Stout disease (GSD), also known as vanishing bone disease, is a rare disorder, which most commonly presents in children and young adults and is characterized by an excessive proliferation of lymphangiomatous tissue within the bones. This lymphangiomatous proliferation often affects the cranium and, due to the proximate location to the dura surrounding cerebrospinal fluid (CSF) spaces, can result in CSF leaks manifesting as intracranial hypotension with clinical symptoms to include orthostatic headache, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Our literature search found only 13 patients with GSD who presented with abnormalities in CSF and intracranial pressure ( Table 1). [1][2][3]5,[7][8][9]11,12,[14][15][16]18 In most patients, a CSF leak was identified from the osteolytic skull base bone. There has been no case report of a patient with GSD complicated by a CSF leak from the thigh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our literature search found only 13 patients with GSD who presented with abnormalities in CSF and intracranial pressure ( Table 1). [1][2][3]5,[7][8][9]11,12,[14][15][16]18 In most patients, a CSF leak was identified from the osteolytic skull base bone. There has been no case report of a patient with GSD complicated by a CSF leak from the thigh.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 13 reported patients with an abnormality in the CSF in the literature, 4 showed increased intracranial pressure. 7,11,15,16 Peragallo et al reported rebound intracranial hypertension (56 cm H 2 O) after the treatment of a CSF leak from the temporal bone in a patient with GSD. 16 The case initially presented with intracranial hypotension and meningitis that occurred from a CSF leak.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment is applied if patients complain about severe pain and impaired function (7,37,38), if there is a fracture or a high risk of fracture, or if complications occur such as an increased intracranial pressure (39) or chylothorax (40) that need surgical intervention. Surgery can consist of removal of the affected bone tissue, with subsequent reconstruction by the use of bone grafts, prostheses, or both.…”
Section: Treatmentmentioning
confidence: 99%